Halal Malaysia logo or brand: the hidden gap - Wan Ismail, Wan Rusni; Othman, Mohhidin; Abdul Rahman, Russly; Kamarulzaman, Nitty Hirawaty; Ab. Rahman, Suhaimi (Elsevier, 2016)
Halal logo is the most common graphic mark use for Halal Malaysia which is a symbol to indicate the product or business is certified Halal by JAKIM. This is also an indication that the product or business is Shariah compliance. The issue of whether Halal Malaysia is logo or brand has not yet being highlighted in any previous study. However, discussion on Halal logo is more predominant where Halal logo was found to have a significant impact on consumer's decision making but such findings merely scratch the surface on the importance issues of Halal branding. Using the qualitative in-depth interview, different findings have emerged pointing to the serious issues in relation to Halal Malaysia brand equity that need to be rectified immediately. Such a problem has never been discussed before because previous findings showed that consumers possess strong awareness toward Halal logo and Halal logo itself has become the main cue that determine consumers final decision making. This has lead to an illusion of strong brand equity which concealed the hidden problem and without proper acknowledgement such problem can lead to serious complication for instance equity dilution. Indeed, Halal Malaysia from logo point of view is very important in determining consumer's awareness and recognition but the issue is only focusing on the surface. On the other hand, brand offer wider perspectives which focus more on the underlying problem or opportunity because brand has value that require constant audit and maintenance in order to ensure its survival.